Children obesity awareness campaign - Wan Mohd Fauzi, Wan Mohamad Faisal (Universiti Teknologi MARA, Perak, 2023)
Children Obesity Awareness is a campaign to create awareness to the public especially parents about the dangers of obesity to children: an issue which many people may underestimate. it is also to help individuals out there such as parents, children and also other people obtain a better understanding of how much losing 'weight' can change life to a better one. we are in collaboration with the Kementerian Kesihatan Malaysia (KKM), will join hands to help people out there especially children because they are still young and may not yet be aware of the dangers and risks that will come as a result of this obesity.